Renal AA amyloidosis: survey of epidemiologic and laboratory data from one nephrology centre - Potysová, Z; Merta, M; Tesar, V; Jancová, E; Honsová, E; Rysavá, R (International urology and nephrology, 2009)
Renal amyloid involvement results, especially, from AL (primary) or AA (secondary) amyloidosis. The extent of amyloid tissue deposits in the kidneys and the clinical course of amyloidosis not only depend on the type of basic process but also reflect the time of diagnosis and the ability to affect the underlying disease. We analyzed laboratory and clinical data from patients with bioptically proven renal amyloidosis. Renal amyloidosis was found in 99 patients (4.65%) from an overall number of 2,128 renal biopsies (RB) performed in our department during a period of 11 years (from 1995 to 2006). AA amyloidosis was diagnosed in 46 patients. Nephrotic syndrome was diagnosed in 27 patients (59%) with AA amyloidosis; all these patients had different degrees of proteinuria. Impaired renal function was discovered in 24 patients (52%); in three of these patients (6.5%) we had to start renal replacement therapy. Patients were treated with corticosteroids, disease-modifying antirheumatic drugs (DMARDs), and biological therapy in various regimens. Nine patients (19.5%) died during the one-year follow-up period; complications such as sepsis and cardiac failure were the leading causes of death. Median survival in the AA group was 54 months. Although for approximately half of patients different treatment regimens can lead to a partial remission or disease stabilization, the prognosis of patients with amyloidosis could be regarded as unsatisfactory.
Keywords: nemoci ledvin; dospělí; Sex Distribution; zdravotnické přehledy; hodnocení rizik; Female; Prednisolone; chronické selhání ledvin; rozložení podle pohlaví; prednisolon; nefrotický syndrom; Adult; ženské pohlaví; Nephrotic Syndrome; Immunohistochemistry; lidé; Survival Analysis; Drug Therapy, Combination; Risk Assessment; Kidney Diseases; imunohistochemie; stupeň závažnosti nemoci; prognóza; Kidney Failure, Chronic; kohortové studie; neparametrická statistika; Middle Aged; Incidence; Cohort Studies; retrospektivní studie; Nephrology; amyloidóza; Age Distribution; Male; jehlová biopsie; incidence; Aged; Amyloidosis; Czech Republic; Antirheumatic Agents; Biopsy, Needle; věkové rozložení; Kidney Function Tests; kombinovaná farmakoterapie; Prognosis; analýza přežití; Česká republika; vyšetření funkce ledvin; lidé středního věku; Statistics, Nonparametric; senioři; mužské pohlaví; nefrologie; Health Surveys; antirevmatika; Severity of Illness Index; Retrospective Studies; amyloid; Amyloid; Humans